Indonesia vs. Thailand: Legal Challenges in Sustainable Agriculture - Ampuan Situmeang; Nipon Sohheng; Ninne Zahara Silviani; Shenti Agustini; Shelvi Rusdiana (JURNAL AKTA, 2024)
Agriculture, as a significant contributor to carbon emissions and climate change, needs to not only change its ways to a more sustainable practice but also revisit what has long been considered conventional agriculture practices to support sustainable development. This requires a comprehensive legal framework to ensure that the transition to sustainable agriculture is supported by structured and streamlined legal compliance that can balance stakeholders’ interests. Employing the comparative legal research method, this study aims to analyze the potentials and challenges of applying sustainability in agriculture, using the comparison between Indonesia and Thailand. The findings of this study suggest that Indonesia’s legal framework for sustainable agriculture, focusing on its single Sustainable Agriculture Law, is more comprehensive than Thailand’s multiple regulations, effectively supporting sustainability across various agricultural processes. This framework aligns well with SDGs 2, 12, 13, and 15, which are crucial for agricultural sustainability. Conversely, Thailand faces challenges due to normative gaps and requires a more unified legal framework to address these SDGs adequately.